Social determinants of health and treatment decisions in head and neck cancer. Issue 2 (10th December 2021) - Shehan, Jennifer N.; Alwani, Tooba; LeClair, Jessica; Mahoney, Taylor F.; Agarwal, Pratima; Chaudhry, Salil T.; Wang, Judy J.; Noordzij, Jacob Pieter; Tracy, Lauren F.; Edwards, Heather A.; Grillone, Gregory; Salama, Andrew R.; et al.
Abstract: Background: This study compares select social determinants of health (SDOH) with treatment modality selection and treatment completion in head and neck cancer (HNC) patients, to better understand disparities in health outcomes. Methods: A retrospective cohort study of HNC ( n  = 1428) patients was conducted. Demographic and disease‐specific variables were recorded, including treatment modality selection and completion. Data were analyzed using two‐sample t tests, chi‐square, and Fisher's exact tests. Results: Primary language was significantly associated with treatment choice, where non‐English speakers were less likely to choose treatment as recommended by the Tumor Board. Lower mean distance from the hospital (37.38 [48.31] vs. 16.92 [19.10], p  < 0.0001) and a county‐based higher mean percentage of bachelor degree or higher education (42.16 [8.82] vs. 44.95 [6.19], p  < 0.0003) were associated with treatment selection. Conclusion: Language, distance from the hospital, and education affected treatment selection in this study and may be useful in understanding how to counsel patients on treatment selection for HNC.